Quantification of PtdInsP3 molecular species in cells and tissues by mass spectrometry - Clark, J; Anderson, K; Juvin, V; Smith, T; Karpe, F; Wakelam, M; Stephens, L; Hawkins, P (2011)
Class I phosphoinositide-3-kinase (PI3K) isoforms generate the intracellular signaling lipid, phosphatidylinositol(3,4,5)trisphosphate (PtdIns(3,4,5)P 3). PtdIns(3,4,5)P 3 regulates major aspects of cellular behavior, and the use of both genetic and pharmacological intervention has revealed important isoform-specific roles for PI3Ks in health and disease. Despite this interest, current methods for measuring PtdIns(3,4,5)P3 have major limitations, including insensitivity, reliance on radiolabeling, low throughput and an inability to resolve different fatty-acyl species. We introduce a methodology based on phosphate methylation coupled to high-performance liquid chromatographyg-mass spectrometry (HPLC-MS) to solve many of these problems and describe an integrated approach to quantify PtdIns(3,4,5)P3 and related phosphoinositides (regio-isomers of PtdInsP and PtdInsP2 are not resolved). This methodology can be used to quantify multiple fatty-acyl species of PtdIns(3,4,5)P3 in unstimulated mouse and human cells (≥105) or tissues (≥0.1 mg) and their increase upon appropriate stimulation. © 2011 Nature America, Inc. All rights reserved.